Outcomes of cases with elevated 3-hydroxyisovaleryl carnitine report from the newborn screening program - Fuad Al Mutairi; Randa Alkhalaf; Abdul Rafiq Khan; Ali Al Othaim; Majid Alfadhel (Molecular Genetics and Metabolism Reports)
Background: Elevated plasma levels of 3-hydroxyisovaleryl-carnitine (C5OH) and impaired leucine catabolism are frequently observed in newborn screening reports, necessitating consideration of various diseases in the differential diagnosis. This study aimed to analyze different forms of C5OH and explore their potential predictive value for diagnosis and outcomes. Methods: A retrospective review of newborn screening positive cases for C5OH-related diseases from May 2011 to December 2023 was conducted. Clinical, biochemical, and molecular phenotypes of all confirmed positive cases during this period were examined. Results: A total of 15 true positive cases were diagnosed. No significant correlation was found between the C5OH levels in newborn screening and the diagnosis of specific C5OH-related disorders or the presence of metabolic, neonatal, or developmental abnormalities. Outcomes varied based on the spectrum of diseases. Conclusion: These findings indicate that relying solely on C5OH levels from newborn screening is insufficient for making accurate diagnoses or predictions regarding C5OH-related disorders. Further comprehensive evaluation and consideration of additional factors are essential for accurate diagnosis, management and outcome.